'Moatifs' of masculinity: The stories told about 'men' in British newspaper coverage of the Raoul Moat case. (April 2013) - Ellis, Anthony; Sloan, Jennifer; Wykes, Maggie
This article addresses the common omission and/or obfuscation of men in accounts of crime and particularly accounts of violence, despite the overwhelming presence of men in violent activities and, indeed, crime per se. In doing so it identifies key themes that frame masculine identities. Using the case of Raoul Moat, the piece analyses the discourses available in British newspapers to account for male violence. Raoul Moat killed one man, injured his ex-partner and a police officer and finally shot himself dead in the Northumbrian wilderness. Whereas most accounts of male violence blame 'bad' women, race, youth, terror, gangs and madness, here news stories evoked different tales of domestic, institutional and elemental masculinity. The themes of those tales, we argue, constitute broad contexts for constructing masculine identities and our analysis offers new insights into how masculine identity is constructed through discourse and why violence is a significantly male-dominated activity; insights which address some of the lacks in current theoretical work on both masculinity and violence.